The Mediating Effect Of Overall Satisfaction On Relationship Between Indoor Environmental Quality And Work Performance: Evidences From Occupants Of Green Buildings In Malaysia - Monsefi, Setareh (2013)
Buildings are recognized as a key contributor to the climate change mitigation, so they have been receiving increased attention in recent years in terms of design, performance and evaluation. Sustainable green buildings can deliver energy and resource efficiency, along with providing a comfortable, healthy and productive environment for occupants.